Long-Term Pain Treatment Did Not Improve Sleep in Nursing Home Patients with Comorbid Dementia and Depression: A 13-Week Randomized Placebo-Controlled Trial - Blytt, Kjersti M.; Husebo, Bettina; Flo, Elisabeth; Bjorvatn, Bjørn (Frontiers in Psychology, 2018)
Objective: Previous research indicates that pain treatment may improve sleep among nursing home patients. We aimed to investigate the long-term effect of pain treatment on 24-hour sleep patterns in patients with comorbid depression and dementia. Design: A 13-week, multicenter, parallel-group, double-blind, placebo-controlled randomised clinical trial conducted between August 2014 and September 2016. Setting: Long-term patients from 47 nursing homes in Norway. Participants: We included 106 patients with comorbid dementia and depression according to the Mini Mental Status Examination (MMSE) and the Cornell Scale for Depression in Dementia (CSDD). Intervention: Patients who were not using analgesics were randomised to receive either paracetamol (3 g/day) or placebo tablets. Those who already received pain treatment were randomised to buprenorphine transdermal system (max. 10 µg/hour/7 days) or placebo transdermal patches. Measurements: Sleep was assessed continuously for 7 days by actigraphy, at baseline and in week 13. Total sleep time (TST), sleep efficiency (SE), sleep onset latency (SOL), wake after sleep onset (WASO), early morning awakening (EMA), and number of wake bouts (NoW) were evaluated. In addition, daytime total sleep time (DTS) was estimated. Pain was assessed with Mobilization-Observation-Behavior-Intensity-Dementia-2 Pain Scale (MOBID-2). Results: The linear mixed model analyses for TST, SE, SOL, WASO, EMA, NoW and DTS showed no statistically significant differences between patients who received active pain treatment and those who received placebo. Post-hoc subgroup analyses showed that there were no statistically significant differences between active treatment and placebo from baseline to week 13 in patients who were in pain (MOBID-2 ≥ 3) at baseline, or in patients who had poor sleep (defined as SE < 85%) at baseline. Patients who received active buprenorphine showed an increase in TST and SE compared to those who received active paracetamol. Conclusion: The main analyses showed that long-term pain treatment did not improve sleep as measured with actigraphy. Compared to paracetamol, TST and SE increased among patients who received buprenorphine. This could indicate that some patients had beneficial effects from the most potent pain treatment. However, based on the present findings, long-term pain treatment is not recommended as a strategy to improve sleep. Clinical Trial https://clinicaltrials.gov/ct2/show/NCT02267057